2020
DOI: 10.3390/app10031099
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Association between Candida Prevalence, Species Specificity, and Oral Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis— Candida and OSCC

Abstract: The present review is a qualitative and quantitative analysis of the overall prevalence of Candida, and its species specificity in oral squamous cell carcinoma (OSCC). PubMed, Scopus, and Web of Science databases were searched using the keywords ‘Candida and oral squamous cell carcinoma’. Only case-control observational studies in the English language evaluating the prevalence and species specificity of Candida in OSCC were included. 297 articles were identified (PubMed-106, Scopus-148, Web of Science-43) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…This study showed Candida albicans to be the most common species found among cancer patients, followed by that Candida tropicalis which was similar to that of the studies carried out by Schelenz and Safdar et al [38,39]. The most common non-Candida species among cancer patients was Candida glabrata, as reported in some studies [40][41][42][43][44]. This is also in agreement with the findings of Abidullah et al, who reported the presence of C. glabrata in patients with oral squamous cell carcinoma [40].…”
Section: Discussionsupporting
confidence: 87%
“…This study showed Candida albicans to be the most common species found among cancer patients, followed by that Candida tropicalis which was similar to that of the studies carried out by Schelenz and Safdar et al [38,39]. The most common non-Candida species among cancer patients was Candida glabrata, as reported in some studies [40][41][42][43][44]. This is also in agreement with the findings of Abidullah et al, who reported the presence of C. glabrata in patients with oral squamous cell carcinoma [40].…”
Section: Discussionsupporting
confidence: 87%
“…OSCC are most often preceded by clinically apparent oral potentially malignant disorders (OPMD).The presence of Candida species in oral leukoplakia has strengthened its association to with OSCC as well [3]. Candida species have been linked to etiopathogenesis of OSCC and oral potentially malignant disorders considering its potential to nitrosylate N-benzyl methylamine [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that C . albicans produces carcinogens such nitrosamines, which have the ability to activate proto-oncogenes and cause carcinomatous alterations ( 105 ). A C .…”
Section: Oral Bacteria Associated With Osccmentioning
confidence: 99%
“…This adhesion can weaken the host's defense mechanisms, allowing for further infection (104). Additionally, it has been shown that C. albicans produces carcinogens such nitrosamines, which have the ability to activate proto-oncogenes and cause carcinomatous alterations (105). A C. albicans infection-related chronic inflammation may also play a role in the development of cancer.…”
Section: Candidamentioning
confidence: 99%